Relationship between serum 25-hydroxyvitamin D concentration and risks of metabolic syndrome in children and adolescents from Korean National Health and Nutrition Examination survey 2008-2010 - Dong Yup Lee; Ah Reum Kwon; Jung Min Ahn; Ye Jin Kim; Hyun Wook Chae; Duk Hee Kim; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2015)
PurposePrevious studies have revealed many inconsistent results regarding the relationship between vitamin D and metabolic syndrome. The purpose of our study was to investigate the association between serum 25-hydroxyvitamin D (25(OH)D) concentration and factors that characterize metabolic syndrome in Korean children and adolescents.MethodsWe analyzed data from 2,880 children and adolescents aged 10-18 years collected from the 2008-2010 Korean National Health and Nutrition Examination Survey. We investigated the data according to quartiles of 25(OH)D concentrations.ResultsSystolic blood pressure and diastolic blood pressure with adjustment for sex and age differed significantly between the serum 25(OH)D groups and exhibited negative trend as 25(OH)D concentrations increased. The number of subjects with metabolic syndrome was greater in the low 25(OH)D groups (I, II, and III quartile) than in the high 25(OH)D group (IV quartile) (P=0.029). BMI and waist circumference were lower in the high 25(OH)D group. Serum 25(OH)D concentration correlated negatively with homeostasis model assessment estimate of insulin resistance (ρ=-0.073, P<0.001) and correlated positively with quantitative insulin sensitivity check index (ρ=0.095, P<0.001).ConclusionLow serum 25(OH)D level is associated with an increase of insulin resistance and metabolic syndrome in children and adolescents.